Engineering ethics - Fleddermann, Charles B. (Pearson, 2014)
Engineering Ethics serves as both a textbook and a resource for the study of engineering ethics. It is written to help future engineers be prepared for confronting and resolving ethical dilemmas that they might encounter during their professional careers.